Analysis Of Project Time Control for the Batulicin Port Road Using the Earned Value Concept Method - Muhammad Taufik Novianto; Budi Witjaksana; Hanie Teki Tjendani (LPPM of NAROTAMA UNIVERSITY, 2025)
Pelaksanan Proyek Jalan Pelabuhan Batulicin merupakan proyek yang penting karena jalan akses The implementation of the Batulicin Port Road Project is an important project because the current access road to Batulicin Port is inadequate. The project execution faced obstacles, including delays in the availability of skilled workers and construction laborers/workers at the project site, delays in the arrival of materials due to required pre-order (indent) and a relatively long manufacturing process at the factory. In the first week up to the third week, the achieved progress was above the planned schedule, and in the fourth week, the achieved progress was below the expected plan. In the fifth week, the achieved progress was above the expected schedule, but in the sixth week up to the tenth week, the achievement progress was again below the planned progress. The fluctuations in progress must be monitored comprehensively in terms of time to estimate the time required for project completion. To resolve these problems, a method used for project control is the Earned Value Analysis (EVA) method. Earned Value Analysis is a tool used in project management that integrates cost and time. The earned value concept presents three dimensions: the physical completion of the project (the percent complete), which reflects the budgeted cost absorption, the actual costs incurred or what is called the actual cost, and what is obtained from the costs incurred or what is called the earned value. The research results show that for time performance (Schedule Performance Index), the value is less than 1, indicating that the project's performance is slower than the planned schedule. The Estimate All Schedule (EAS) value shows a value of 277 days, which is 37 days longer than the planned schedule.